An inclusion of willingness to pay as an independent variable in the individual travel cost model - Matthew, Nitanan Koshy; Shuib, Ahmad; Ramachandran, Sridar; Herman, Syamsul (2013)
The economic value of the resources available at a site can be shown in terms of the benefits gained by the visitors in a quantitative or monetary value. The benefits gained by the visitors could be estimated by using the demand of visitors to the site using the concept of consumer surplus. Travel cost method (TCM) is an alternative technique that can be used to determine the value of environmental resources based on the demand curve. There have been various modifications made to the basic TCM developed by Hotelling 1947. Modification of the basic TCM will take into account those factors that may shift the demand of visitors. The objectives of this article are to review the basic TCM, to modify the basic TCM through the incorporation of willingness to pay (WTP) as one of the independent variables in the ITCM model and finally discuss the role of WTP as an independent variable in the ITCM model. Structured interview or face to face data collection method was employed to obtain the primary data on the WTP of visitors for an entrance fee to the study site using a well developed questionnaire. ITCM model will be estimated with the Poisson regression and Negative Binomial analysis using the LIMDEP software. The modification of the basic TCM is crucial to improve and enhance the environmental valuation techniques. The incorporation of WTP in the ITCM is expected to enhance the fit of the model in turn improving the consumer surplus estimation.